AB0709 Risk Factors of Digital Ulcers in Patients with Systemic Sclerosis: An Observational Study From a Single Center in South Korea. (9th June 2015) - Jung, K.H.; Park, W.; Kwon, S.R.; Lim, M.J.
Abstract : Background: Digital ulcer (DU) is a significant cause of pain, functional disability and quality-of-life impairment in patients with systemic sclerosis (SSc). DU can occur even in patients with very early/early SSc (called the "window of opportunity" of SSc). Therefore, the identification of risk factors of DU can improve the SSc outcome. Several large cohort studies have reported risk factors of DU in SSc [1]. However, the risk factors of DU in patients with SSc have not been described in Korea yet. Objectives: To determine the prevalence and risk factors of DU in Korean patients with SSc. Methods: Ninety consecutive SSc patients with at least 6 months of follow-up were enrolled from January 2014 to December 2014 in tertiary hospital rheumatism center. Demographic data, clinical characteristics, internal organ involvements, comorbidities, laboratory findings, and disease-specific factors were obtained through medical records and patients interviews, retrospectively. Results: Thirty-seven patients (41%) had a history or present digital ulceration and 43% of them had recurrent DU. Patients with DU were thin, had higher modified Rodnan skin score (mRSS), showed frequent pigmentation, microsomia, finger flexion contracture, acroosteolysis and calcinosis. They had anti-Scl 70 antibody, advanced nailfold capillary changes (active and late pattern) and interstitial lung disease more frequently than in patients without DU (Table 1. ). In a multiple logistic regression analysis, mRSS (OR =1.178, 95% C.I. =1.06-1.31, p-value =0.002) was the sole risk factor of DU. A nailfold capillary microscopic finding was the only risk factor of recurrence of DU (p-value =0.025). Conclusions: In Korean SSc patients, Rodnan skin score is a risk factor of DU and advanced nailfold capillary change is a risk factor for recurrent DU. We need more attention to treat those SSc patients with high mRSS and advanced nailfold capillary change. References: Silva I, Almeida J, Vasconcelos C. A PRISMA-driven systematic review for predictive risk factors of digital ulcers in systemic sclerosis patients. Autoimmun Rev. 2015;14(2):140-152 Disclosure of Interest: None declared